The role of the community pharmacy work system in the enactment of pharmacists' non-technical skills - Ashour, Ahmed; Ashcroft, Darren M.; Phipps, Denham L. (Ergonomics, 2025)
Non-technical skills are recognised as important in various work domains, but have been the subject of debate regarding their role in ergonomics/human factors, given their focus on human behaviour itself rather than the interaction between people and systems. This study aimed to examine the relationship between non-technical skills and the work system in which they are enacted. The study setting was community pharmacies in England. Qualitative data were obtained from observation of seven pharmacists and semi-structured interviews with 16 pharmacists, and subjected to thematic analysis. Elements of their work system were found to be related to their non-technical skills; either by creating a need for the skill in the first place, or by facilitating or inhibiting its enactment. The findings highlight the importance of considering the work system that contextualises individuals' and teams' behaviour, in addition to the behaviour itself, when investigating non-technical skills. The obvious focus of interventions to enhance non-technical skills is the behaviour of individuals and teams. However, we highlight the importance of considering the work system within which people are operating, as this forms the context within which non-technical skills are exercised. We suggest particular ways in which the work system might influence the exercise of non-technical skills.